The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1557/jmr.2019.176
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of interactions of ‘blood-nano interface’ of carbon-based nanomaterials for biomedical applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Among various allotropic forms of carbon, CNTs, which were discovered by Iijima in 1991, are another type of widely studied carbon‐based nanomaterials. [ 77,78 ] Arc‐discharge evaporation and chemical vapor deposition techniques are usually used to prepare CNTs. [ 77 ] Lin et al.…”
Section: Types Of Carbon‐based Fluorescent Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among various allotropic forms of carbon, CNTs, which were discovered by Iijima in 1991, are another type of widely studied carbon‐based nanomaterials. [ 77,78 ] Arc‐discharge evaporation and chemical vapor deposition techniques are usually used to prepare CNTs. [ 77 ] Lin et al.…”
Section: Types Of Carbon‐based Fluorescent Nanomaterialsmentioning
confidence: 99%
“…[ 77,78 ] Arc‐discharge evaporation and chemical vapor deposition techniques are usually used to prepare CNTs. [ 77 ] Lin et al. prepared multiwalled CNTs by the chemical vapor deposition method.…”
Section: Types Of Carbon‐based Fluorescent Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It determines the safety and, as a whole, the biocompatibility of NP and the effectiveness of treatment methods based on them, as well as the choice of analytical methods when using NP as a probe (biolabel, biosensor). Understanding of the mechanisms of interaction is important both for fundamental knowledge and for further development of applications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ishii introduced the current research status of nano-carbon-based thyroidectomy in China, analyzed some problems in nano-carbonbased thyroidectomy, proposed related solutions, and pointed out that nano-carbon is used as a tracer in resection; it plays an important role in surgery (6). Singh et al took 89 patients undergoing thyroidectomy under general anesthesia with remifentanil as experimental subjects, and conducted an analysis and research on the anesthesia effect of remifentanil, and found that 15 remifentanil has great potential to induce anesthesia hyperalgesia, among 89 patients, 13 had anesthesia hyperalgesia (7). Jiang et al introduced the relevant principles of the anesthetic effect of remifentanil in the article, pointed out that the analgesic effect of remifentanil disappeared too quickly when used for surgical anesthesia, and easily caused anesthesia hyperalgesia, and analyzed the related technology to overcome this problem (8).…”
Section: Introductionmentioning
confidence: 99%